Online On-the-Fly Testing of Real-time Systems - Mikucionis, Marius; Larsen, Kim G.; Nielsen, Brian (BRICS Report Series, 2003)
In this paper we present a framework, an algorithm and a new tool for online testing of real-time systems based on symbolic techniques used in UPPAAL model checker. We extend UPPAAL timed automata network model to a test specification which is used to generate test primitives and to check the correctness of system responses including the timing aspects. We use timed trace inclusion as a conformance relation between system and specification to draw a test verdict. The test generation and execution algorithm is implemented as an extension to UPPAAL and experiments carried out to examine the correctness and performance of the tool. The experiment results are promising.